(untitled) (Albayan Scientific Journal, 2023)
The study targeted to identify the degree of availability of time management methods for secondary school principals and their assistants in AIN ZARA region, from their own point of view, the researcher adopted the descriptive approach, and the study population consisted of all secondary school principals and their assistants in AIN ZARA region, The number of (14) of them (7) are managers, and (7) are their assistants, 100% of their total number. The sample was selected using a comprehensive inventory method; for the purpose of achieving the objectives of the study, a questionnaire was developed consisting of (36) items distributed among the dimensions of the study, and the reliability coefficient was calculated by the method of internal consistency according to Cronbach’s alpha equation for the dimensions and the tool as a whole, The results of the study indicated that the averages of administrative methods used by secondary school principals and their assistants in the AIN ZARA region were very high, As for the averages of the paragraphs of the obstacle practices of time management among secondary school principals and their assistants, they were of a low degree, and the researcher included several recommendations in her study, the most important of which are: Holding courses and training programs for the managers of the secondary school principals and their assistants to provide them with time management methods, especially for those with little or medium experience.